Study of fracture properties and post-peak softening process of rubber concrete based on acoustic emission. (27th December 2021) - Liu, Miaoyan; Lu, Jun; Ming, Pan; Yin, Yangyang
Highlight: The post-peak softening behavior of rubber concrete was studied. The softening section of rubber concrete increases with the amount of rubber content. b -values, AF and RA explain well the prolonged softening process of rubber concrete. Abstract: To investigate the effect of rubber content on the softening behavior of concrete after fracture, three-point bending fracture tests under quasi-static loading were carried out on plain concrete and rubber concrete beams with rubber content of 10%, 20%, and 30% respectively. The loading process was also monitored in real-time using the AE technique. By analyzing the test results, it was found that the mixing of rubber extended the crack extension process and increased the deformation capacity of the concrete, the rubber particles played a role in relieving the stress concentration at the crack tip during the crack extension process, and enhanced the softening characteristics of the concrete and extended the softening process of the concrete. At the same time, the softening process of the concrete was studied combined with changes in AE amplitude and it was found that when the amount of rubber content increased, fewer cracks appeared within the rubber concrete and the size of the cracks decreased. The change in b -value indicated that the content of rubber particles in concrete not only prevented the appearance of cracks inside the concrete but also prevented the expansion of cracks. Finally, the analysis of the change curves of RA and AF revealed that the transformation of the form of cracks appearing inside the concrete from tensile cracks to shear cracks was the reason for the extension of the softening process of the rubber concrete.